1977
DOI: 10.1002/cne.901730311
|View full text |Cite
|
Sign up to set email alerts
|

Descending pathways from the superior colliculus: An autoradiographic analysis in the rhesus monkey (Macaca mulatta)

Abstract: The autoradiographic tracing method has been used to identify the various descending tectofugal pathways and their targets in the rhesus monkey (Macaca mulatta). The present data reveal that the majority of descending tectofugal axons arise from collicular laminae which lie ventral to the stratum opticum (layer 3). Such descending axons can be grouped into two major bundles or tracts, i.e., the ipsilateral tectopontine-tectobulbar tract and the crossed tectospinal tract (or the predorsal bundle). There is, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
145
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 435 publications
(157 citation statements)
references
References 75 publications
11
145
1
Order By: Relevance
“…It was further identified as a structure that is involved in the generation of patterned locomotion (Shik and Orlovsky, 1976). Because the SC projects to the nucleus cuneiformis (Harting, 1977), electrical microstimulation in the intermediate and deep layers could activate the above-mentioned movement patterns. This possibility is especially interesting because, in the present study, defense-like behavior was sometimes but rarely observed after electrical microstimulation (but see DesJardin et al, 2013).…”
Section: Collicular Contribution To Complex Behaviormentioning
confidence: 99%
“…It was further identified as a structure that is involved in the generation of patterned locomotion (Shik and Orlovsky, 1976). Because the SC projects to the nucleus cuneiformis (Harting, 1977), electrical microstimulation in the intermediate and deep layers could activate the above-mentioned movement patterns. This possibility is especially interesting because, in the present study, defense-like behavior was sometimes but rarely observed after electrical microstimulation (but see DesJardin et al, 2013).…”
Section: Collicular Contribution To Complex Behaviormentioning
confidence: 99%
“…The intermediate layer of the SC projects to the b subnucleus of the caudal medial accessory olive (Frankfurter et al 1976;Harting 1977;Huerta and Harting 1984), which, in turn, projects to lobule VII of the vermis (Kralj-Hans et al 2007). Quasi-visual (QV) neurons in the SC (Mays and Sparks 1980), which start discharging 80 -90 ms after a target step and cease firing only when the saccade is executed (and the error is eliminated), could be the source of this visual error signal.…”
Section: Error Signals and Saccade Adaptationmentioning
confidence: 99%
“…The midline cerebellum, which is part of a parallel route for oculomotor information from the superior colliculus (SC) to reach the premotor brain stem generator for saccades (Harting 1977;Kralj-Hans et al 2007;Noda et al 1990;Yamada and Noda 1987), has been implicated as a structure where signals are adapted to reduce saccade dysmetria. It consists of the oculomotor vermis (lobules VIc and VII) and the caudal fastigial nucleus to which they project.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, saccade adaptation might influence neurons in the NRTP, which receives direct inputs from the SC (Harting 1977;Kawamura et al 1974;Scudder et al 1996), and, in turn, projects directly to the oculomotor vermis (Brodal 1980;Shinnar et al 1975;Thielert and Thier 1993;Yamada and Noda 1987) and to the CFN (Gonzalo-Ruiz and Leichnetz 1990;Noda et al 1990). Therefore, we investigated whether activity in the NRTP is changed during saccade adaptation.…”
Section: Introductionmentioning
confidence: 99%